1992
DOI: 10.1007/bf02050328
|View full text |Cite
|
Sign up to set email alerts
|

What is the meaning of colorectal transit time measurement?

Abstract: This study was done to understand the different available methods used to calculate colorectal transit times. A single abdominal radiograph is taken following six successive daily ingestions of the same number of identical radiopaque markers. This method correlates well (P less than 0.001) with that using a single ingestion of markers with daily x-ray films until total expulsion. In techniques used to measure colorectal transit time with multiple ingestion of markers, the number of days of ingestion depends on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
132
0
11

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(143 citation statements)
references
References 20 publications
0
132
0
11
Order By: Relevance
“…Retention of 10 or more markers in the right colon, left colon or rectosigmoid were de®ned as colonic inertia, hindgut dysfunction and outlet obstruction respectively. 8,20,22 The ®nding of 10 or more markers gathered in more than one sector was considered a mixed pattern. Xrays taken every 5 days categorized the abnormal CTTs as follows: moderate, when more than 10 markers were seen until the tenth day; severe, when more than 10 markers were seen until the ®fteenth day; and very severe when 10 or more markers were noted at 20 or more days.…”
Section: Methodsmentioning
confidence: 99%
“…Retention of 10 or more markers in the right colon, left colon or rectosigmoid were de®ned as colonic inertia, hindgut dysfunction and outlet obstruction respectively. 8,20,22 The ®nding of 10 or more markers gathered in more than one sector was considered a mixed pattern. Xrays taken every 5 days categorized the abnormal CTTs as follows: moderate, when more than 10 markers were seen until the tenth day; severe, when more than 10 markers were seen until the ®fteenth day; and very severe when 10 or more markers were noted at 20 or more days.…”
Section: Methodsmentioning
confidence: 99%
“…We identified one robust systematic review, 4 included studies that reported data that enabled calculation of sensitivity and specificity, 4,5,32,33 and two more recent studies (Table IV). 24,25 All studies except one 24 were performed in referred children.…”
Section: Abdominal Radiographymentioning
confidence: 99%
“…The methodology is not standardized in radiopaque marker and the abdomen plain X-ray film taken time. A positive result was defined as more than 20% of the radiopaque marker remaining on day five (120 h later), as indicative of slow transit time according to a plain X-ray film of the abdomen [14].…”
Section: Investigationsmentioning
confidence: 99%